Analysis Of The Effect Of Inflation, Rupiah Exchange Rate, Bank Size, LDR, Bopo And Car On Non-Performing Loans (Case Of Conventional Commercial Banks Registered In BEI For The 2016 To 2020 Period) - Maulana, Nurnita Hayatun; Gursida, Hari; Hardiyanto, Arief Tri (UNIVERSITAS PAKUAN, 2024)
The impact of COVID-19 on the Indonesian economy is inevitable, at least on the financial market, due to the weakening of economic growth due to the corona virus pandemic. Banks on a small scale are also at risk of bad credit because they continue to provide loans to debtors. Banks do not only focus on collecting funds from customer deposits, the funds that have been collected are channeled back to the community in the form of loans or credit. This is done so that the money accumulated in the bank can continue to operate, the risk is quite large and can threaten the health of the bank, the most haunting bank is bad credit (NPL - Non-Performing Loan). NPL is a threat to sustainable development for developing countries. The purpose of this research is to look at the effect of inflation, exchange rates (exchange rates), LDR (Loan Deposit Ratio), BOPO (Operating Costs to Operating Income) and CAR (Capital Adequacy Ratio) on NPLs at conventional banks in 2016−2020. The research method is quantitative research based on positive philosophy, used to examine certain populations or samples, sampling techniques are generally carried out randomly, data collection uses research instruments, data analysis is quantitative/statistical in nature with the aim of testing hypotheses that are has been established. The results of the study show that conventional commercial banks listed on the IDX for the period 2016 to 2020 Inflation has no effect on non-performing loans. The Rupiah Exchange Rate has no effect on Non-Performing Loans. Size has no effect on Non-Performing Loans. Size has no effect on Non-Performing Loans. LDR has an effect on Non-Performing Loans. CAR has no effect on Non-Performing Loans.